The Association between Within-Visit Blood Pressure Variability and Carotid Artery Atherosclerosis in General Population - Li, Yan (Public Library of Science, 2014)
OBJECTIVES: To determine whether within-visit blood pressure (BP) variability based on three measurements over minutes is associated with increased carotid intima-media thickness (IMT) and plaque in a general population. METHODS: A cross-sectional survey was performed in 2007, and a total of 1222 Beijing community residents aged 50–79 years belonging to part of the Chinese Multi-Provincial Cohort Study (CMCS) were recruited in this study. BP was measured three times at 5-minute intervals during a single visit, and the maximum absolute difference (MAD) between any two readings of three measurements was used to indicate within-visit BP variability. Carotid IMT and plaque scanned by B-mode ultrasound were identified as the surrogate end points in the intermediate stage of atherosclerosis. RESULTS: After adjustment for established cardiovascular risk factors, the odds ratio (OR) (95% confidence interval (CI)) for increased carotid IMT and internal carotid plaque associated with the highest within-visit diastolic BP (DBP) variability (MAD > mean + standard deviation (SD)) compared with participants in the lowest within-visit DBP variability (MAD ≤ mean −SD) was 4.92 (1.48–16.42) and 6.07 (1.31–28.10), respectively, in the normotensives (P = 0.01; P = 0.02). The OR (95% CI) for internal carotid plaque associated with the highest within-visit systolic BP (SBP) variability (MAD >mean +SD) compared with participants in the lowest within-visit SBP variability (MAD ≤ mean −SD) was 3.54 (1.26–10.00) in the hypertensives on antihypertensive therapy (P = 0.02). CONCLUSIONS: Within-visit DBP variability was associated with increased carotid IMT and internal carotid plaque in the normotensive population, and within-visit SBP variability was associated with internal carotid plaque in hypertensive patients undergoing antihypertensive therapy.